The influence of Japanese automotive industry investment in East Nógrád - Tóth, Arnold; Csongrádi, Gyöngyi; Engelberth, István (Észak-magyarországi Stratégiai Füzetek, 2024)
This study explores Japanese-Hungarian economic relations, specifically focusing on foreign direct investments (FDI) in Hungary. The analysis delves into the historical development and current state of Japanese capital flow into Hungary, with a particular emphasis on the automotive industry. Foreign direct investments are shown to enhance productivity through technology transfer and foster positive impacts on corporate relationships, contributing to economic growth. The study demonstrates the mutual benefits of Japanese FDI in the Hungarian automotive industry and includes a case study on the activities of a Japanese company in Hungary, examining its role in the regional labour market.